If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -24b + -16 + 25b + -6 = 0 Reorder the terms: -16 + -6 + -24b + 25b = 0 Combine like terms: -16 + -6 = -22 -22 + -24b + 25b = 0 Combine like terms: -24b + 25b = 1b -22 + 1b = 0 Solving -22 + 1b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '22' to each side of the equation. -22 + 22 + 1b = 0 + 22 Combine like terms: -22 + 22 = 0 0 + 1b = 0 + 22 1b = 0 + 22 Combine like terms: 0 + 22 = 22 1b = 22 Divide each side by '1'. b = 22 Simplifying b = 22
| -4u^2+9u-3= | | 12-7x=-44 | | 3(y-3)+y=2(6+2y) | | 12x-4/3y=11 | | 1/4(32x-16)=6x | | 0.05/10 | | -8X-13=5X | | 0.2b+0.1=0.12b-0.06 | | (2x+5/7x-5)/(3x/7x-5) | | 9y-2-4y=-27 | | 4y+4=-2y-8 | | 0.19y+0.05(y+2000)=1540 | | 63d+63n=5.05 | | -21-x-2x=30 | | 9.12/x=0.2 | | 63(n+d)=5.05 | | 8t+1/9=t+9/18+t-7/18 | | 3xy+2x+3x= | | -(x+4)-2x+3=-16 | | 2x+3x+400=1050 | | 4b+3=2b | | 49x^4+112x^2+64=0 | | M+t=r | | 25(x+39)=b | | 3.5(3x-8)=x | | -(3-15y)=12 | | -(6x-3)=-9 | | 3-6x=2+6x | | 1/3(12x-36)+4=x+25 | | 5k-3/2=4 | | 2b+5=b+13 | | xy-4x=12 |